Erfaringer fra mit Land-Liv i Østerhanherred. (Fortsat fra 4de Bind, S . 79.) - Dreyer, J. G. B. (Tidsskrift for Landøkonomi, 2018)
Erfaringer fra mit Land-Liv i Østerhanherred. (Fortsat fra 4de Bind, S . 79.)